2009
DOI: 10.3390/rs1020068
|View full text |Cite
|
Sign up to set email alerts
|

Use of Macro Fibre Composite Transducers as Acoustic Emission Sensors

Abstract: Abstract:The need for ever lighter and more efficient aerospace structures and components has led to continuous optimization pushing the limits of structural performance. In order to ensure continued safe operation during long term service it is desirable to develop a structural health monitoring (SHM) system. Acoustic emission (AE) offers great potential for real time global monitoring of aerospace structures, however currently available commercial sensors have limitations in size, weight and adaptability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Lee and Kuo [21] design a miniature acoustic transducer with two conical PZT elements to measure the surface wave velocity by using PZT ceramic (PZT-5H) as the sensing element. Other piezoelectric elements reported in literature for AE sensing are polyvinylidene fluoride-trifluonoethylene (PVDF-TrFE) copolymer [22], embedded polyvinylidene fluoride (PVDF) [23], PTCa/PEKK piezo-composites [24,25], piezoelectric polymer-ceramic composites [26], macro-fiber composite (MFC) film [27].…”
Section: Piezoelectric Acoustic Emission (Ae) Sensorsmentioning
confidence: 99%
“…Lee and Kuo [21] design a miniature acoustic transducer with two conical PZT elements to measure the surface wave velocity by using PZT ceramic (PZT-5H) as the sensing element. Other piezoelectric elements reported in literature for AE sensing are polyvinylidene fluoride-trifluonoethylene (PVDF-TrFE) copolymer [22], embedded polyvinylidene fluoride (PVDF) [23], PTCa/PEKK piezo-composites [24,25], piezoelectric polymer-ceramic composites [26], macro-fiber composite (MFC) film [27].…”
Section: Piezoelectric Acoustic Emission (Ae) Sensorsmentioning
confidence: 99%
“…To test the performance of the proposed algorithm, macro fiber composite (model MFC-M2814) sensors manufactured by Smart Material Inc., with an active area of 28 mm x 14 mm and a bandwidth of kHz, were used. The typical physical structure of an MFC sensor is formed by rectangular piezoceramic fibers locked in an epoxy matrix and sandwiched between two arrays of integrated electrodes (see for example (Eaton, et al, 2009) for details). The rectangular piezoceramic fibers are arranged in a regular spacing and precise parallel alignment to form the MFC transducer.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…This value is close to that reported in the literature and indicates that monitoring of the vibrational modes up to a 0.4 m distance (considering the distance among the sensors in the experimental setup) should be feasible. The directionality sensitivity is also a concern with MFC sensors (Eaton, et al, 2009). To characterize the response of a typical MFC sensor, a set of preliminary tests was carried out on a thin aluminum plate with dimensions of 600 x 600 mm 2 and 1.9 mm in thickness.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…One of the most prominent MFC utilizations is linked to health monitoring systems and the evaluation of damages (Park et al, 2006;Hameed et al, 2009). MFC sensors are capable of recording AE and detecting damages (Eaton et al, 2009). Some vibration tests under optimal running conditions revealed that the monitoring and control can be done with a limited number of actuators, which reduces costs (Sohn et al, 2011).…”
Section: Mfc Is a Composite Technology Originally Developed At The Namentioning
confidence: 99%